Illusory Perceptions in Academic Writing in English - Donaghue, Edward (Lyuboslovie, 2024)
Academic writing is a key component of learning in institutions of higher education, and plays a vital role in assessment. However, many students have illusory perceptions about the nature of academic writing. The purpose and process of writing, and the processes involved in knowledge-construction, meaning-making, and argumentation in academic writing in English are not always transparent, and students often fail to make effective use of feedback. In addition, many teachers also have perceptual illusions about writing and, as a result of a lack of adequate training in providing instruction and appropriate feedback on writing, fail to dispel their students’ perceptual illusions and effectively develop their academic writing skills. In an attempt to outline the nature of such illusions, this paper provides a review and analysis of key research on teaching and providing feedback on academic writing. It considers writing at university as product, process, discourse, and genre, and finds that questions of what constitutes effective feedback, and how feedback can improve student writing, are inextricably linked with approaches to the teaching of writing. The findings suggest that approaches to teaching writing and approaches to feedback on writing can both be seen as part of a developmental and interactive process of scaffolding student writing skills in which process and socio-constructive models of teaching and learning are most effective. Raising the awareness of both teachers and students about the nature of writing, and the purpose of feedback, could play a crucial role in dispelling students’ illusory perceptions, and improving their academic writing skills.